Risk Factors for Canine Osteoarthritis and Its Predisposing Arthropathies: A Systematic Review - Anderson, Katharine L.; Zulch, Helen; O'Neill, Dan G.; Meeson, Richard L.; Collins, Lisa M. (Frontiers in Veterinary Science, 2020)
Osteoarthritis is a common clinical and pathological end-point from a range of joint disorders that ultimately lead to structural and functional decline of the joint, with associated lameness and pain. Increasing our understanding of the risk factors associated with osteoarthritis will assist us to address the significant threat it poses to the welfare of the dog population and implement preventive measures. Here we present the first comprehensive systematic review and evaluation of the literature reporting risk factors for canine osteoarthritis. We aimed to systematically collate, review and critically evaluate the published literature on risk factors for canine osteoarthritis and its predisposing conditions such as developmental joint dysplasias, cruciate ligament degeneration, and patellar luxation. We systematically searched peer-reviewed publications for both osteoarthritis and predisposing arthropathies on Web of Science and PubMed following PRISMA (2009) guidelines, using pre-specified combinations of keywords. Sixty-two papers met the inclusion criteria and were evaluated and graded on reporting quality. Identified risk factors included both modifiable factors (neuter status and body weight) for which intervention can potentially affect the risk of occurrence of osteoarthritis, and unmodifiable factors (sex, breed and age) which can be used to identify individuals most ‘at risk’. Osteoarthritis in dogs frequently develops from predisposing arthropathies, and therefore risk factors for these are also important to consider. Papers evaluated in this study were rated as medium to high-quality; gap analysis of the literature suggests there would be significant benefit from additional research into the interactions between and relative weighting of risk factors. There are a number of examples where research outcomes are conflicting such as age and sex; and further investigation into these factors would be beneficial to attain greater understanding of the nature of these risks. Comprehensively collating the published risk factors for osteoarthritis and its predisposing conditions offers opportunities to identify possible means for control and reduction within the population through preventative methods and control strategies. We highlight these factors, as well as current literature gaps where further research is warranted, to aid future research direction.